PERSEPSI MAHASISWA FAKULTAS EKONOMI DAN PELAKU BISNIS MENGENAI PENTINGNYA ETIKA BISNIS BERDASARKAN GENDER DAN USIA - Pribadi, Angelia; Rambe, Rizky Fillhayati (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2015)
This study aims to prove there is a difference of perception about the importance of business ethics education. In this study has three hypotheses to be tested are differences in the perception of the importance of ethics education among business people and students. Further testing of the difference principle importance of business ethics education among women da the men. Finally, this study also examines the differences in perception among the older age group and younger age groups. Respondents in this study consisted of 300 respondents from business people and students who take a course in entrepreneurship and ethics profesi.Masing each hypothesis tested first normality test data is then tested with independent sample T-test.The test results prove that only one proved the hypothesis significantly different perceptions regarding the importance of business ethics education between employers and mahasiswa.Sedangkan two hypotheses that examine differences in the perception of the importance of business ethics education between women and men do not have either the absolute differences, as well as statistics , While the latter hypothesis that examine differences in the perception of the importance of business ethics education between older and younger age groups showed an absolute difference, but not statistically significant.Â